“Technology Reshaping the Future of Industry” The Impact of Electronics HRM on Organization Performance with Mediating Role of IT Training, An Extension of Institutional System Theory - Shahid, Muhammad Naeem; Malik, Ayesha; Azhar, Tehseen; Iqbal, Muhammad Shahid (Pakistan Journal of Humanities and Social Sciences, 2023)
Technology is the most powerful tool, which is used to redesign the organizational structures. The scaling and acceleration of human capabilities, the automation of labour, and the creation of new methods for obtaining and supplying labour are all having a substantial impact on the nature of work in the future. The success of an organisation depends on the growth of its people resources. This essay presents a perspective on the idea of electronics HRM on organisational performance with the mediating role of IT training in Pakistan's textile industry. To carry out the investigation, a quantitative methodology was employed. All of the study's participants were employees, and the study's 300 samples were drawn using the stratified sampling technique. Using the PLS program and structural equation modelling, the study's hypothesis was tested. The study's findings showed a clear connection between operational, rational, and transformational electronic human resource management (E-HRM) and the organisational performance of the textile sector. A study also shown that IT training significantly improved organisational effectiveness. Finally, IT training acts as a mediator between EHRM and organisational performance. Therefore, the main contribution of the current study is to illuminate the untapped potential of IT training for the effective implementation of e-HRM procedures and its effects on organisational performance.